Development and Optimization of Antisolvent Cooling Coupled Crystallization Process for Coenzyme Q10. Issue 7 (28th March 2022) - Li, Qiuju; Liu, Yihang; Liu, Baoshu; Sun, Hua
Abstract: The solubility of coenzyme Q10 in binary mixed solvents (tetrahydrofuran (THF) + ethanol) is determined at the temperature range from 278.15 to 313.15 K by static high‐performance liquid chromatography. The super‐solubility of coenzyme Q10 at f C = 0.4(C is ethanol), f C = 0.6, f C = 0.8 is measured by dynamic laser method, thus the metastable zone of coenzyme Q10 in binary mixed solvent (THF + ethanol) is obtained. The measurement results show that the solubility of coenzyme Q10 and the width of the metastable zone increase with the increasing of temperature and increasing of THF content in the mixed solvent. Coenzyme Q10 antisolvent cooling coupled crystallization process is developed based on thermodynamic data, and the crystallization conditions are investigated experimentally. The diameter span of crystal size distribution decreases from 5.542 to 1.981 and the median particle size ( Dv 50) increases from 41.8 to 81.3 μm,  which means that the crystal products of coenzyme Q10 are improved by adjusting the crystallization process parameters. Abstract : Based on the crystallization thermodynamics investigation, a new process of antisolvent cooling coupled crystallization of coenzyme Q10 is developed, with which the DS of coenzyme Q10 crystals is reduced from 5.542 to 1.981, and the Dv 50 is increased from 41.8 to 81.2 μm. The quality of coenzyme Q10 crystals is improved by adjusting the crystallization process parameters.